RP-HPLC method for simultaneous estimation of simvastatin and ezetimibe in tablet dosage forms - Srikanth Choudary Pallothu; Jogu Chandrudu; Sriram. N (International Journal of Pharmacy and Analytical Research, 2018)
A rapid, precise, specific, accurate and robust simple RP-HPLC method for the simultaneous determination of Simvastatin and Ezetimibe has been developed and validated. The Stationary phase (column) is Inertsil-ODS C18 (250 x 4.6 mm, 5 µ) and Mobile Phase is Methanol: Acetonitrile (80:20), with flow rate of 1.0ml/min using UV detection at 240 nm. The retention time if simvastatin and ezetimibe is 3.125 and 3.380 respectively. The Method shows linearity in the range of simvastatin and ezetimibe with correlation coefficient of 0.9999 for both. The limit of detection (LOD) and limit of quantification (LOQ) for simvastatin and ezetimibe were found to be 0.22 and 0.25 respectively. The % recovery for simvastatin and ezetimibe were found within the range of 99.83 and 99.55 respectively. The developed RP-HPLC method was innovation, suitable for detecting both simvastatin and ezetimibe in tablet dosage form.